Risk Factors Associated with the Development of Immune-Checkpoint Inhibitor Diabetes Mellitus: An Integrative Review - Vivian Crowder; Veronica Brady (Life)
Immune checkpoint inhibitor diabetes mellitus (ICI-DM) is an emerging phenomenon in the adult oncology population, with an increased incidence reflecting the increased use of immunotherapy; however, risk factors for ICI-DM have not been fully identified. The aim of this integrated literature review was to synthesize the published literature on ICI-DM and the factors associated with an increased risk for its development. The review was guided by Sanieszko’s Epidemiology Triad theoretical framework. We conducted a literature search using the Cumulative Index to Nursing and Allied Health Literature, Web of Science, and PubMed databases. The analysis included 2030 studies that met the search criteria, 23 of which were peer-reviewed articles that met the inclusion criteria. The results demonstrated a positive relationship between older age, medical history of diabetes, the presence of susceptible alleles, and exposure to immunotherapy, with an increased risk for ICI-DM. Future studies should include larger samples, more diverse populations, and a broad range of institutions to confirm the risk factors associated with ICI-DM.